Efficient one-pass chase soft-decision BCH decoder for multi-level cell NAND flash memory - Xinmiao Zhang; Jiangli Zhu; Yingquan Wu (2011 IEEE 54th International Midwest Symposium on Circuits and Systems (MWSCAS), 2011)
BCH codes are adopted in multi-level cell NAND flash memory to increase the storage reliability. Compared with hard-decision decoding of BCH codes, the soft-decision Chase algorithm can achieve significant coding gain by carrying out decoding trials on 2 η test vectors. To reduce the complexity of the Chase decoding, a one-pass scheme can be employed to derive the error locators of all test vectors in one run. In this paper, a novel technique is first proposed to reduce the latency and simplify the computation scheduling of the one-pass Chase decoding. Then efficient architectures are developed for the modified one-pass decoding. The hardware complexity of the proposed decoder with η = 4 is analyzed for a (4200, 4096) BCH code. Compared to other soft-decision BCH decoding algorithms, it can achieve much better performance-complexity tradeoff.